Determinants of tobacco smoking abstinence one year after major noncardiac surgery: a secondary analysis of the VISION study. (October 2022) - Ofori, Sandra N.; Marcucci, Maura; Mbuagbaw, Lawrence; Conen, David; Borges, Flavia K.; Chow, Clara K.; Sessler, Daniel I.; Chan, Matthew T.V.; Hillis, Graham S.; Pettit, Shirley; Heels-Ansdell, Diane; Devereaux, Philip J.; et al.
Abstract: Background: Tobacco smoking is a leading preventable cause of death and increases perioperative risk. Determinants of smoking abstinence after noncardiac surgery and the association between smoking and 1-yr vascular outcomes are not fully elucidated. Methods: We did a prospective cohort study of 40 004 patients, aged ≥45 yr, enrolled between August 2007 and November 2013, and followed for 1 yr after surgery. Patients were categorised as never smokers, ex-smokers (quit >4 weeks preoperatively), and current smokers (smoking ≤4 weeks preoperatively). Primary outcome was abstinence at 1 yr. Secondary outcome was a composite of all-cause death, non-fatal myocardial infarction, and non-fatal stroke at 1 yr. Results: Of 4658 current smokers, 1838 (39.5%) were abstinent 1 yr after surgery. Median (inter-quartile range) time to resumption was 7 (3–23) days post-surgery. Perioperatively, 7.2% of current smokers obtained smoking cessation pharmacotherapy. Older age (adjusted risk ratio [aRR] 1.21; 95% confidence interval [CI]: 1.12–1.32); having recent coronary artery disease (aRR 1.41; 95% CI: 1.29–1.55); cancer (aRR 1.37; 95% CI: 1.18–1.59); and undergoing major vascular (aRR 1.20; 95% CI: 1.02–1.41), urgent/emergent (aRR 1.14; 95% CI: 1.05–1.23), or thoracic (aRR 1.41; 95% CI: 1.26–1.56) surgeries increased abstinence. One-year abstinence was less likely when patients stopped smoking 0–1 day (aRR 0.53; 95% CI: 0.43–0.66) and 2–14 days (aRR 0.76; 95% CI: 0.71–0.82) before surgery compared with >14 days before surgery. Current smokers (adjusted hazard ratio [aHR] 1.14; 95% CI: 1.01–1.29) and ex-smokers (aHR 1.11; 95% CI: 1.03–1.21) had higher risk of the 1-yr vascular outcome compared with never smokers. Conclusions: Long-term tobacco abstinence is more likely after major surgery in those with serious medical comorbidities. Interventions to prevent smoking resumption after surgery remain a priority. Clinical trial registration NCT00512109.